Graphene-based electro-catalytic material as well as preparation method and application thereof

By embedding CuNi bimetals in graphene-based catalysts, the problem of poor catalytic performance of existing catalysts during CO2 reduction is solved, and the catalytic effect of lower energy barriers in C-C coupling reaction is achieved, and the efficiency of CO2 reduction to produce C2 products is improved.

CN119824452APending Publication Date: 2025-04-15ANHUI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510017446.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing graphene-based catalysts have poor catalytic performance during CO2 reduction, especially in the C-C coupling reaction, which is difficult to effectively generate C2 products.

Method used

By preparing graphene materials supported by CuNi bimetal embedded with nitrogen-doped graphene, ultrasonic treatment and calcination are used to ensure that Cu and Ni metals are uniformly embedded in the graphene, thus forming an efficient electrocatalyst.

Benefits of technology

The catalyst exhibits a lower energy barrier in the C-C coupling reaction, specifically 0.28 eV and 0.27 eV, which significantly reduces the C-C coupling barrier for *COCOH and *COCHO, improving the efficiency of the CO2 reduction reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824452A_ABST
    Figure CN119824452A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene-based electro-catalytic material as well as a preparation method and application thereof, and belongs to the technical field of electro-catalytic materials. The preparation method comprises the following steps: (1) preparing nitrogen-doped graphene (N-C); (2) preparing a graphene material (Cu-N-C) embedded with Cu metal; and (3) preparing a graphene material (CuNi-N-C) embedded with CuNi bimetal. The graphene-loaded CuNi bimetallic catalyst has the beneficial effects that the graphene-loaded CuNi bimetallic catalyst is low in C-C coupling energy barrier for * COCOH and * COCHO in the CO2 reduction process, a good linear relation exists between adsorption energy of reactants and adsorption energy of products of C-C coupling, and a new thought is provided for optimization of catalyst design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a graphene-based electrocatalytic material and a preparation method and application thereof. Background Art

[0002] With the development of industry and the continuous improvement of people's living standards, energy consumption is also increasing, but clean energy such as wind energy, hydropower, solar energy, geothermal energy, etc. has not been fully developed. So far, fossil fuel energy is still our main energy source. Fossil fuels are exhaustible energy sources that take millions of years to generate, and the consumption rate far exceeds the generation rate. The non-renewable nature of fossil energy and the huge consumption of it by humans have caused fossil energy to gradually become exhausted, which will eventually cause a serious energy crisis. The consumption of fossil fuels is accompanied by environmental problems on which people depend for survival. The large-scale consumption of fossil energy causes greenhouse gas emissions, increases the concentration of greenhouse gases in the atmosphere, enhances the greenhouse effect, and leads to global warming. The electrocatalytic CO2 reduction reaction to obtain more valuable compounds is considered to be an environmentally friendly and effective method that has been deeply explored. It not only solves the greenhouse effect problem, but also produces high-energy-density products, while also alleviating the problem of fossil fuel shortages.

[0003] Generally, people focus on the research of CO2 reduction products on C1 products (such as CO, CH4 and CH3OH, etc.). In recent years, C2 products, such as acetic acid, ethanol, ethylene and ethane, have received more attention due to their higher energy density and wider practical applications. However, carbon dioxide reduction is a complex process, especially the CC coupling step has a high activation energy barrier and is the rate-determining step for the production of C2 products. Although previous studies have made significant progress in reducing CO2 to C2 products, it is still a major challenge to develop efficient catalysts with low activation energy barriers for CC coupling reactions during CO2 reduction. Therefore, it is of great significance to continuously explore efficient CC coupling electrocatalysts for CO2 reduction to produce C2 products.

[0004] In recent years, single-atom catalysts (SACs) have gradually become a hot topic of research due to their high atomic utilization efficiency and excellent catalytic activity. However, studies have shown that single-atom catalysts tend to generate C1 products rather than C2 products during CO2 reduction, which is a significant limitation. In addition to single-atom catalysts, diatomic catalysts (DACs) have also attracted considerable research interest due to their synergistic effects, versatility, controllability, stability and novelty. They are widely considered to be a type of catalyst with great development prospects. In addition, graphene-based carbon materials are often used as carriers in electrocatalytic reactions due to their abundance, versatility in morphology, relatively high conductivity, and controllability that can cause changes in charge and spin density after being doped with various heteroatoms. Therefore, graphene-supported diatomic catalysts are expected to reduce the reaction energy barrier and promote CC coupling reactions.

[0005] The Chinese patent application document with publication number CN116162941A discloses a preparation method, product and application of a graphene-supported cobalt-based bimetallic single-atom electrocatalyst. The catalyst is prepared by using nitrogen-doped graphene as a carrier, loading monodispersed metal cobalt and metal M (M is one of V, Cr, Mn, Fe, Ni, Cu, and Mo). The single-atom cobalt metal content accounts for 0.5-4.0wt% of the weight of the graphene, and the single-atom M metal content accounts for 0.5-4.0wt% of the weight of the graphene. However, the catalytic performance of the catalyst is poor, so it needs to be further improved. Summary of the invention

[0006] The technical problem to be solved by the present invention is how to solve the problem of poor catalytic performance of existing graphene-based catalysts.

[0007] The present invention solves the above technical problems through the following technical means:

[0008] A first aspect of the present invention provides a method for preparing a graphene-based electrocatalytic material, comprising the following steps:

[0009] (1) Preparation of nitrogen-doped graphene (NC): Zeolite imidazolate framework (ZIF-8) was mixed with methanol, dried and then carbonized at high temperature to obtain nitrogen-doped graphene material;

[0010] (2) Preparation of Cu metal embedded graphene material (Cu-NC): Dispersing nitrogen-doped graphene material and Cu(NO3)2 in an organic solvent respectively, and then mixing the two after ultrasonic treatment, stirring, centrifuging, washing, drying, and calcining to obtain Cu metal embedded graphene material;

[0011] (3) Preparation of CuNi bimetallic embedded graphene material (CuNi-NC): Disperse Cu metal embedded graphene material and Ni(NO3)2 in organic solvents respectively, and repeat the steps in (2) to obtain.

[0012] Preferably, in step (1), the high temperature carbonization temperature is 900-1100° C., and the time is 0.5-1.5 h.

[0013] Preferably, in step (2), the mass ratio of nitrogen-doped graphene material and Cu(NO3)2 is (25-30):1, and more preferably 28.6:1.

[0014] Preferably, in step (3), the mass ratio of Cu metal-embedded graphene material and Ni(NO3)2 is (25-30):1, and more preferably 28.6:1.

[0015] Preferably, in steps (2) and (3), the organic solvent is selected from any one or more of methanol, ethanol and n-hexane.

[0016] Preferably, in steps (2) and (3), the drying temperature is 50-80° C. and the drying time is 10-14 h.

[0017] Preferably, in steps (2) and (3), the calcination temperature is 800-1200° C. and the calcination time is 40-80 min.

[0018] The second aspect of the present invention provides a graphene-based electrocatalytic material prepared by the above preparation method.

[0019] The third aspect of the present invention proposes the use of the above-mentioned graphene-based electrocatalytic material in hydrogen evolution reaction or CC coupling catalysis.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention provides a method for preparing a graphene-based electrocatalytic material. The graphene-based electrocatalytic material prepared by the method has good catalytic performance and good activity in hydrogen evolution reaction and CC coupling reaction. The CC coupling performance of the catalyst shows that the CC coupling energy barriers for *COCOH and *COCHO are very low, 0.28 eV and 0.27 eV, which indicates that the catalyst has potential high efficiency in the CO2 reduction process.

[0022] 2. The discovery of the linear relationship between the adsorption energies of reactants and products in CC coupling provides important guidance for optimizing the design of bimetallic catalysts, which helps to better understand the action mechanism of bimetallic catalysts in CC coupling reactions and provides new ideas for the design and synthesis of more efficient catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a schematic structural diagram of a graphene-based material provided in Example 2 of the present invention;

[0024] Figure 2 is a structural STEM image of the graphene-based material provided in Example 1 of the present invention;

[0025] Figure 3 is a HER performance diagram of the graphene-based material provided in Example 1 of the present invention;

[0026] Figure 4 Schematic diagram of two CC coupling mechanisms provided by Example 2 of the present invention;

[0027] Figure 5 This is a coupling energy barrier diagram of the CuNi bimetallic catalyst *CO-*COH provided in Example 2 of the present invention;

[0028] Figure 6 This is the CuNi bimetallic catalyst *CO-*CHO coupling energy barrier diagram provided in Example 2 of the present invention;

[0029] Figure 7 A linear relationship diagram of the initial and final state adsorption energies of *CO-*COH coupling provided in Example 2 of the present invention;

[0030] Figure 8 This is a linear relationship diagram of the initial and final state adsorption energies of *CO-*CHO coupling provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0033] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0034] Embodiment 1:

[0035] A method for preparing a graphene-based electrocatalytic material comprises the following steps:

[0036] (1) Preparation of nitrogen-doped graphene (NC):

[0037] The zeolite imidazolate framework (ZIF-8) was mixed with methanol, then vacuum dried at 60°C overnight, placed in a tube furnace, and heated to 1000°C in an Ar gas flow for 1 hour to obtain a nitrogen-doped graphene material.

[0038] (2) Preparation of Cu metal embedded graphene material (Cu-NC):

[0039] 200 mg of the nitrogen-doped graphene material obtained in step (1) was dispersed in 24 ml of n-hexane and ultrasonicated at room temperature for 1 hour. After a uniform suspension was formed, a Cu(NO3)2 methanol solution (25 mg ml -1 , 280 μL) was ultrasonically treated at room temperature for 10 minutes and then added dropwise to the above solution. Next, the mixed solution was stirred at room temperature for 1 and a half hours. Then, the sample was centrifuged, washed with methanol several times, and vacuum dried at 60°C overnight. Finally, the sample was placed in a tube furnace and heated to 1000°C in an Ar gas flow for 1 hour to obtain a Cu metal-embedded graphene material.

[0040] (3) Preparation of CuNi bimetallic embedded graphene material (CuNi-NC):

[0041] 200 mg of the Cu metal-embedded graphene material obtained in step (2) was dispersed in 24 ml of n-hexane and ultrasonicated at room temperature for 1 hour. After a uniform suspension was formed, a Ni(NO3)2 methanol solution (25 mg ml -1 , 280 μL) was added dropwise to the above solution after ultrasonic treatment at room temperature for 10 minutes. Next, the mixed solution was stirred for another hour at room temperature. The sample was then centrifuged, washed several times with methanol, and dried overnight in a vacuum at 60°C. Finally, the sample was placed in a tube furnace and heated to 1000°C in an Ar flow for 1 hour to obtain a CuNi bimetallic embedded graphene material. Figure 2 The STEM image of the structure proves that the graphene-based bimetallic atomic material has been prepared.

[0042] We performed the hydrogen evolution reaction (HER reaction) on this substrate, such as Figure 3 The CuNi bimetallic embedded graphene material (CuNi-NC) provided 10 mA cm in 1.0 M PBS. -2 The CuNi-NC electrocatalyst exhibits excellent HER activity with a current density (j) of only 8 mV overpotential (Z), which is significantly lower than that of 20% Pt / C (19 mV).

[0043] Embodiment 2:

[0044] The initial configuration was constructed by Material Studio, and the density functional theory (DFT) calculation was implemented using the Vienna First Principles Simulation Package (VASP). The VASP package was used for structural optimization to verify that the graphene-supported CuNi bimetallic catalytic material can exist stably; on the basis of a stable substrate, we built and optimized the CC coupling initial state (IS) *CO-COH / *CO-CHO and final state (FS) *COCOH / *COCHO models respectively; based on the above stable models, we calculated the adsorption energy and reaction energy before and after the CC coupling reaction, and used the climbing image squeeze spring band (CI-NEB) method to search for the transition state (TS) and obtain the kinetic reaction energy barrier, including:

[0045] 1. CuNi co-embedded in graphene material

[0046] Single-atom catalysts (SACs) are characterized by high dispersion. Although this structure is favored in some catalytic processes due to its high atomic efficiency, their single active site shows obvious limitations in CC coupling reactions that require multi-atom collaboration. The lack of necessary multi-atom interactions limits their catalytic activity in complex reactions. In contrast, DACs enable direct atomic interactions by providing two adjacent or close metal atoms on their surface, which is crucial for promoting CC coupling reactions. In this study, we constructed a CuNi bimetallic atom co-embedded graphene electrocatalyst ( Figure 1 ), the diatomic structure of DACs not only ensures the appropriate interatomic distance to effectively stabilize and activate the reaction intermediates and reduce the reaction energy barrier, but also provides multifunctional active sites, in which one metal atom can stabilize one intermediate while the other activates another intermediate, jointly promoting CC coupling.

[0047] 2. Reaction pathway of CC coupling reduction to C2 product

[0048] In the CO2RR process, the CC coupling step is considered to have a high activation energy barrier, which is the key limiting step for the formation of C2-related products. In the study, we found that after the formation of *CO-CO, two major C2-related intermediates are produced: *CO-CHO and *CO-COH. The generation of these intermediates is a crucial link in the CC coupling reaction. In order to explore this process in depth, this study focuses on the two pathways of *CO-COH and *CO-CHO ( Figure 4 ). The blue pathway indicates the CO-COH coupling pathway, and the green pathway indicates the CO-CHO coupling pathway.

[0049] 3. Kinetic energy barrier of CC coupling reaction under CuNi bimetallic catalyst

[0050] In this study, we used the climbing image squeezed spring band (CI-NEB) method to calculate the energy barriers of CC coupling reactions. The CI-NEB method is an effective computational chemistry technique for determining transition states and corresponding energy barriers during reactions. Using this method, we found that the CC coupling energy barriers of CuNi bimetallic catalysts are very low, both below 0.3 eV and 0.28 eV ( Figure 5 ) and 0.27eV( Figure 6 ). This result indicates that the CuNi bimetallic catalyst has high activity in promoting CC coupling reactions and can significantly reduce the reaction energy barrier, thereby improving the efficiency of CO2 reduction reactions.

[0051] 4. Linear relationship between reactant adsorption energy and product adsorption energy

[0052] Although this study focuses on CuNi bimetallic catalysts, considering the diversity of elements, we also expanded the scope of research to include other metal elements including Cr, Mn, Fe, Co, Ni and Cu. By studying these homonuclear and heteronuclear bimetallic combinations, we found that no matter which pathway, the adsorption energies of reactants and products in CC coupling reactions show a significant linear relationship ( Figure 7 )( Figure 8 This discovery has important guiding significance for the design of diatomic catalysts. It not only reveals the effect of different metal element combinations, but also provides a theoretical basis for optimizing the structure and performance of diatomic catalysts. Through this systematic study, we can have a deeper understanding of the mechanism of action of diatomic catalysts in CC coupling reactions, opening up new ways to design and synthesize more efficient and more specific catalysts.

[0053] Based on the above studies, we can see that diatomic catalysts show great potential in the study of CC coupling reactions. Through carefully designed graphene-supported diatomic catalysts, we can not only reduce the energy barrier of CC coupling reactions, but also, by expanding to different metal combinations, we can better understand and utilize the unique properties of diatomic catalysts, thus providing new ideas and strategies for CO2 reduction and other related chemical conversion processes.

[0054] Embodiment 3:

[0055] A method for preparing a graphene-based electrocatalytic material comprises the following steps:

[0056] (1) Preparation of nitrogen-doped graphene (NC):

[0057] The zeolite imidazolate framework (ZIF-8) was mixed with methanol, then vacuum dried at 60°C overnight, placed in a tube furnace, and heated to 900°C in an Ar gas flow for 1.5 hours to obtain a nitrogen-doped graphene material.

[0058] (2) Preparation of Cu metal embedded graphene material (Cu-NC):

[0059] 175 mg of the nitrogen-doped graphene material obtained in step (1) was dispersed in 24 mL of n-hexane and ultrasonicated at room temperature for 1 hour. After a uniform suspension was formed, a Cu(NO3)2 methanol solution (25 mg ml -1 , 280 μL) was ultrasonically treated at room temperature for 10 minutes and then added dropwise to the above solution. Next, the mixed solution was stirred at room temperature for 1.5 hours. Then, the sample was centrifuged, washed with methanol several times, and vacuum dried at 80°C for 10 hours. Finally, the sample was placed in a tube furnace and heated to 1200°C in an Ar gas flow for 40 minutes to obtain a Cu metal-embedded graphene material.

[0060] (3) Preparation of CuNi bimetallic embedded graphene material (CuNi-NC):

[0061] 175 mg of the Cu metal-embedded graphene material obtained in step (2) was dispersed in 24 ml of n-hexane and ultrasonicated at room temperature for 1 hour. After a uniform suspension was formed, a Ni(NO3)2 methanol solution (25 mg ml -1 , 280 μL) was added dropwise to the above solution after ultrasonic treatment at room temperature for 10 minutes. Next, the mixed solution was stirred for another hour at room temperature. The sample was then centrifuged, washed several times with methanol, and dried in a vacuum at 50°C for 14 hours. Finally, the sample was placed in a tube furnace and heated to 800°C in an Ar flow for 80 minutes to obtain a CuNi bimetallic embedded graphene material.

[0062] Embodiment 4:

[0063] A method for preparing a graphene-based electrocatalytic material comprises the following steps:

[0064] (1) Preparation of nitrogen-doped graphene (NC):

[0065] The zeolite imidazolate framework (ZIF-8) was mixed with methanol, then vacuum dried at 60°C overnight, placed in a tube furnace, and heated to 1100°C in an Ar gas flow for 0.5 hours to obtain a nitrogen-doped graphene material.

[0066] (2) Preparation of Cu metal embedded graphene material (Cu-NC):

[0067] 210 mg of the nitrogen-doped graphene material obtained in step (1) was dispersed in 24 mL of n-hexane and ultrasonicated at room temperature for 1 hour. After a uniform suspension was formed, a Cu(NO3)2 methanol solution (25 mg ml -1 , 280 μL) was ultrasonically treated at room temperature for 10 minutes and then added dropwise to the above solution. Next, the mixed solution was stirred at room temperature for 1.5 hours. Then, the sample was centrifuged, washed with methanol several times, and vacuum dried at 50°C for 14 hours. Finally, the sample was placed in a tube furnace and heated to 800°C in an Ar gas flow for 80 minutes to obtain a Cu metal-embedded graphene material.

[0068] (3) Preparation of CuNi bimetallic embedded graphene material (CuNi-NC):

[0069] 210 mg of the Cu metal-embedded graphene material obtained in step (2) was dispersed in 24 ml of n-hexane and ultrasonicated at room temperature for 1 hour. After a uniform suspension was formed, a Ni(NO3)2 methanol solution (25 mg ml -1 , 280 μL) was added dropwise to the above solution after ultrasonic treatment at room temperature for 10 minutes. Next, the mixed solution was stirred for another hour at room temperature. The sample was then centrifuged, washed several times with methanol, and dried in a vacuum at 80°C for 10 hours. Finally, the sample was placed in a tube furnace and heated to 1200°C in an Ar flow for 40 minutes to obtain a CuNi bimetallic embedded graphene material.

[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a graphene-based electrocatalytic material, characterized in that: The following steps are involved: (1) Preparation of nitrogen-doped graphene (NC): Zeolite imidazolate framework (ZIF-8) was mixed with methanol, dried and then carbonized at high temperature to obtain nitrogen-doped graphene material; (2) Preparation of Cu metal embedded graphene material (Cu-NC): Dispersing nitrogen-doped graphene material and Cu(NO3)2 in an organic solvent respectively, and then mixing the two after ultrasonic treatment, stirring, centrifuging, washing, drying, and calcining to obtain Cu metal embedded graphene material; (3) Preparation of CuNi bimetallic embedded graphene material (CuNi-NC): Disperse Cu metal embedded graphene material and Ni(NO3)2 in organic solvents respectively, and repeat the steps in (2) to obtain.

2. The preparation method according to claim 1, characterized in that: In step (1), the high temperature carbonization temperature is 900-1100° C. and the time is 0.5-1.5 h.

3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of nitrogen-doped graphene material and Cu(NO3)2 is (25-30):

1.

4. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of Cu metal embedded graphene material and Ni(NO3)2 is (25-30):

1.

5. The preparation method according to claim 1, characterized in that: In steps (2) and (3), the organic solvent is selected from any one or more of methanol, ethanol and n-hexane.

6. The preparation method according to claim 1, characterized in that: In steps (2) and (3), the drying temperature is 50-80° C. and the drying time is 10-14 h.

7. The preparation method according to claim 1, characterized in that: In steps (2) and (3), the calcination temperature is 800-1200° C. and the calcination time is 40-80 min.

8. The preparation method according to claim 7, characterized in that: In steps (2) and (3), the calcination temperature is 1000° C. and the calcination time is 60 min.

9. A graphene-based electrocatalytic material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the graphene-based electrocatalytic material according to claim 9 in hydrogen evolution reaction or CC coupling catalysis.

Citation Information

Patent Citations

  • Method for preparing CuO / porous carbon composite wave-absorbing material with ZIF-67 as template

    CN105694810A

  • Preparation method of novel nano carbon material and electrocatalytic hydrogen production application of novel nano carbon material

    CN106732613A

  • Preparation method of heat storage / catalysis integrated material

    CN112827495A

  • Method for preparing super activated carbon based on zeolite-like imidazate framework compound and application

    CN113321211A